2013
DOI: 10.1080/17437199.2011.569937
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic pain–emotion relations in chronic pain: a theoretical review of moderation studies

Abstract: Running head: DYNAMIC PAIN-EMOTION RELATIONS 2Current developments in chronic pain research are changing the focus in the study of pain-emotion relations from the identification of general patterns to the study of dynamic and context-related interactions manifesting both within and between individuals. This shift towards understanding variation at both intra-and interpersonal levels has significant clinical implications for psychological adjustment to chronic pain conditions, and thus represents an important t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 104 publications
(70 reference statements)
0
9
0
Order By: Relevance
“…This is consistent with a recent review exploring the pain-emotion relationship in adult persistent pain populations indicating that poor sleep may strengthen the association between high pain and emotional distress. 84 Additionally, there is evidence that positive emotions act as a protective factor in the pain-sleep relationship. Studies in SCD 20 and JIA 15 found that the influence of poor sleep on high pain the following day was weakened at increasing levels of positive mood.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with a recent review exploring the pain-emotion relationship in adult persistent pain populations indicating that poor sleep may strengthen the association between high pain and emotional distress. 84 Additionally, there is evidence that positive emotions act as a protective factor in the pain-sleep relationship. Studies in SCD 20 and JIA 15 found that the influence of poor sleep on high pain the following day was weakened at increasing levels of positive mood.…”
Section: Resultsmentioning
confidence: 99%
“…Even among those researchers who believe in a causal link between these conditions, there is no agreement regarding the direction of the causality. In fact, a complete picture of this relationship would be much more complex, acknowledging the moderating role of individual and contextual factors, such as personality traits, cognitive styles, physiologic mechanisms, or social support, among others (42). In this systematic review we attempted to investigate a single/simple facet of this complex association and bring some light into the field.…”
Section: Discussionmentioning
confidence: 99%
“…Current developments in chronic pain research are changing their focus regarding the study of pain–emotion relations, shifting from the identification of general patterns to the study of dynamic and context‐related interactions manifesting both within and between individuals . A recent review study has analysed the associations between pain and emotion in chronic pain (including fibromyalgia patients), as well as the possible mediating and moderating variables in these relations.…”
Section: Introductionmentioning
confidence: 99%